Уродженці білоруських губерній у Глухівському учительському інституті в добу імперії Романових - Крижанівський, В.М. (Сіверщина в історії України, 2021)
У статті проаналізовано вклад Глухівського учительського інституту в підготовку білоруської інтелігенції в 1880 – 1910-х рр.
За вище окреслений період в учительському інституті отримали системну освіту не менше ніж 29 литвинів. Більшість із них
не повернулися на Батьківщину та брали активну участь у науковій і освітній діяльності на теренах Росії, України та Лівану. The purpose of the study is to understand the role of the Hlukhiv
Teachers’ Institute in the training of the Belarusian intelligentsia in 1885–
1911. The research methodology is based on principles of historicism,
scientificity, and systematics. Historical-generic and historical-systemic
methods are used to disclose the defined theme in the article. Scientific
novelty. The issue of teaching Belarusians in teacher’s college during
the Romanov empire were determined based on a wide range of sources
Hlukhiv Teacher’s Institute became an important center for training
teachers at the turn of the XIX–XX centuries. 29 natives of the Belarusian
provinces studied at the institute. Lithuanian-Belarusians received
high-quality knowledge and realized themselves in the system of education
and science. P. Chubov, Y. Rybchynskyi, P. Feshchenko, A. Shako,
M. Leshchenko, M. Kaminskyi, O. Stasevych, M. Sak, S. Furs, O. Mohylnytskyi
realized themselves in the education system in Ukraine, Belarus,
Russia. A. Lesyk was elected a deputy from the Labor Party to the State
Duma. A. Lesyk became a famous Belarusian public figure and teacher-
methodologist after the First World War. V. Monich studied at the
Kharkiv Institute of Technology and Charlottenburg Polytechnic after
graduating from the Teacher’s Institute. He became a famous scientist
on the problems of steam locomotive, taught at the Kharkiv Institute
of Technology. N. Yaroshevich studied at the Moscow Institute of Agriculture
after graduating from the Teachers’ Institute. N. Yaroshevich
headed the Belarusian State Polytechnic Institute in 1920. He was
arrested in 1921. N. Yaroshevich moved to Uzbekistan to avoid arrest.
He worked at the Central Asian State University, the Institute of Irrigation
and Agricultural mechanization.